2018
DOI: 10.1080/00222895.2018.1485009
|View full text |Cite
|
Sign up to set email alerts
|

Head and Trunk Movements During Turning Gait in Children with Cerebral Palsy

Abstract: Thirty children with cerebral palsy (CP) and 22 typical developing (TD) were tested with 3D-gait analysis. At turning, trunk rotation was larger in CP2 (GMFCS II) than in TD and CP1 (GMFCS I), and head flexion was larger in CP3 (GMFCS III) than TD. Maximum head and trunk flexion values during the entire trial were larger in CP3 than in the other groups, and trunk flexion was larger in CP2 than in TD. Trial time increased with GMFCS-level. Less trunk rotation than TD and CP1 reflects spatial insecurity in CP2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…The selected articles with characteristics findings have been shown in Tables 2 and 3. [13] 2018 Cross-sectional 52 30 22 9.1-11.7 1-3 [14] 2017 Cross-sectional 72 52 20 8.5-14.5 1-2 [15] 2016 Cross-sectional 52 30 22 9.1-11.7 1-3 [16] 2016 Cross-sectional 40 20 20 2-9 1-3 [4] 2016 Cross-sectional 50 26 24 4-12 -17] 2014 Cross-sectional 36 16 20 8-14 - [18] 2014 Cross-sectional 40 23 17 8-18 - [19] 2014 Cross-sectional 34 17 17 5-18 1-3 [20] 2014 Cross-sectional 114 92 22 0-25 1-3 [6] 2014 Cross-sectional 32 16 16 9-13 1-2 [21] 2014 Cross-sectional 70 41 29 5-18 1-3 [22] 2014 Cross-sectional 107 92 15 5-30 1-3 [23] 2014 Cross-sectional 20 20 0 5-15 1-2 [24] 2013 Cross-sectional 100 100 0 8-15 1-3 [12] 2013 Cross-sectional 40 20 20 2-10 1-2 [25] 2011 Cross-sectional 56 26 30 8-15 1-3 [26] 2013 Cross-sectional 48 31 17 11-26 1-2 [27] 2013 Cross-sectional 149 122 27 17-23 1-3…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The selected articles with characteristics findings have been shown in Tables 2 and 3. [13] 2018 Cross-sectional 52 30 22 9.1-11.7 1-3 [14] 2017 Cross-sectional 72 52 20 8.5-14.5 1-2 [15] 2016 Cross-sectional 52 30 22 9.1-11.7 1-3 [16] 2016 Cross-sectional 40 20 20 2-9 1-3 [4] 2016 Cross-sectional 50 26 24 4-12 -17] 2014 Cross-sectional 36 16 20 8-14 - [18] 2014 Cross-sectional 40 23 17 8-18 - [19] 2014 Cross-sectional 34 17 17 5-18 1-3 [20] 2014 Cross-sectional 114 92 22 0-25 1-3 [6] 2014 Cross-sectional 32 16 16 9-13 1-2 [21] 2014 Cross-sectional 70 41 29 5-18 1-3 [22] 2014 Cross-sectional 107 92 15 5-30 1-3 [23] 2014 Cross-sectional 20 20 0 5-15 1-2 [24] 2013 Cross-sectional 100 100 0 8-15 1-3 [12] 2013 Cross-sectional 40 20 20 2-10 1-2 [25] 2011 Cross-sectional 56 26 30 8-15 1-3 [26] 2013 Cross-sectional 48 31 17 11-26 1-2 [27] 2013 Cross-sectional 149 122 27 17-23 1-3…”
Section: Resultsmentioning
confidence: 99%
“…In our review, we found that the most common motion analysis tool used for kinematics was VICON motion analysis system [4,13,15,18,20,22,23,26,33] whereas for kinetics force platform was common in practice [7,28]. The details on motion analysis system could be seen from Table 3.…”
Section: Instrumentation and Motion Analysis Systemmentioning
confidence: 98%
See 3 more Smart Citations